2009
DOI: 10.1007/s00709-009-0069-0
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative defence reactions in sunflower roots induced by methyl-jasmonate and methyl-salicylate and their relation with calcium signalling

Abstract: Ca(2+) plays a critical role as second messenger in the signal-response coupling of plant defence responses, and methyl-jasmonate and methyl-salicylate are important components of signal transduction cascades activating plant defences. When intact axenic non-induced seedling roots of sunflower were treated with different Ca(2+) concentrations up to 1 mM, there was no significant increase in O(2)(*-) generation or DMAB-MBTH peroxidase (extracellular, ECPOX) activities in the apoplast, probably because these roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Both are key compounds in the shikimic acid pathway and are involved in the induction of direct and indirect plant defenses (Dicke and Hilker 2003). A previous study suggested that as part of plant defense response, MeSA induces an oxidative burst in sunflower seedling roots (Garrido et al 2009) and is produced by various plants in response to herbivore damage (Van Den Boom et al 2004;Gadino et al 2012) and also attracts natural enemies of mites including P. persimilis, Aphis glycines (Matsumura) (Dicke et al 1990;Mallinger et al 2011), Chrysopa nigricornis (Burmeister), Hemerobius sp. (Linnaeus), Deraeocoris brevis (Akbulatova), Stethorus punctum picipes (Casey), and Orius tristicolor (White) (James and Price 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Both are key compounds in the shikimic acid pathway and are involved in the induction of direct and indirect plant defenses (Dicke and Hilker 2003). A previous study suggested that as part of plant defense response, MeSA induces an oxidative burst in sunflower seedling roots (Garrido et al 2009) and is produced by various plants in response to herbivore damage (Van Den Boom et al 2004;Gadino et al 2012) and also attracts natural enemies of mites including P. persimilis, Aphis glycines (Matsumura) (Dicke et al 1990;Mallinger et al 2011), Chrysopa nigricornis (Burmeister), Hemerobius sp. (Linnaeus), Deraeocoris brevis (Akbulatova), Stethorus punctum picipes (Casey), and Orius tristicolor (White) (James and Price 2004).…”
Section: Discussionmentioning
confidence: 98%
“…MeSA and SA are key compounds in the shikimic acid pathway and are involved in the induction of direct and indirect plant defenses (Dicke & Hilker 2003). MeSA is an important component of the signal transduction cascades, which activate the plant defense response, and it induces an oxidative burst in sunflower seedling roots (Garrido et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Epinephrine (also called adrenaline) has been used to detect O 2 • as after the reaction with O 2 • , the absorbance of the reaction product, adrenochrome, can be measured (at about 490 nm; [319]). Epinephrine has been used to measure O 2 • from chestnut seeds [320] and spinach chloroplasts [313], extracellular O 2 • production from bryophytes and lichens [281] and roots [191], and mitochondrial O 2 • production from barley roots [321]. This method is not specific to O 2 • , as epinephrine has been shown to react also with H 2 O 2 [322], and therefore specificity assays are always needed (see e.g.…”
Section: Dyes Nbt Nbd and Xtt Nitro Blue Tetrazolium (Nbt) Is A Tramentioning
confidence: 99%
“…The effects of ubiquitous plant metabolites on the MBTH-DMAB signal call for special care to assure that the signal actually reflects the H 2 O 2 content of the study material. The MBTH/DMAB method has been used to measure the increase in extracellular peroxidase activity in sunflower roots during defense signaling [191].…”
Section: Dyesmentioning
confidence: 99%